Civic Pageantry in Early Modern London: Contexts and New Research Methodologies - Pikli, Natália (Hungarian Journal of English and American Studies, 2021)
Book reviews: Finlayson, J. Caitlin and Amrita Sen, eds. Civic Performance. Pageantry and Entertainments in Early Modern London. Abingdon-New York: Routledge, 2020. xiv + 254 pages. ISBN 978-1-138-22839-9. Hb. £96.